Estudio de factibilidad para la creación de un empresa productora y comercializadora de bolsos y zapatos en cuero para los estratos 3,4 y 5 de la ciudad de Pereira Risaralda. (2015)
This feasibility study is the creation of the exodus SAS company, which will be devoted to the development and marketing of articles of leather, especially bags and footwear for the modern woman, which will have the value added not only a high quality product, but also the possibility that people can define their own style through custom designs. To define the feasibility of the company, it is initially from the methodological aspect that is important to give a focus to the project, then begins working with market research, to analyze demand applies to a defined sample survey to female sex at levels 3, 4 and 5 of the city of Pereira After questions relevant on the acceptance of products, the information is tabulated and are graphics for both qualitative and quantitative, analysis in this way are determined some features that are important to customers and which should be adjusted in the project; for the analysis of the offer the different actors of the market, including competition, which has certain deficiencies that can be leveraged in favour of the company are evaluated. Subsequently the technical study was performed, in which is en el cual se define defined the size of the company, according to standards to comply with the requirements by the clients, in the same way is defines the location of plant production and marketing, which is decided to be in the city of Pereira, identifies the necessary machinery, labor and raw material required for the operation of the company. This step environmental impact analyses also notably with the use of waste of leather, as well as the strategies that must be implemented to counter it. The administrative and legal structure of the company is defined in the same way. Conclusion if the company is viable in all aspects, is the financial study, this allows you to identify costs and expenses, as well as the financial evaluation of the project which is very useful, since it allows decisions right in favors of the implementation of the project, by the yields that this throws.